Urban cyclists' perspectives on post-collision behaviour change: A qualitative study. (May 2015) - Jachyra, Patrick; Atkinson, Michael; Bandiera, Glen
Highlights: Post-collision cycling behaviours are examined with 18 urban cyclists. Cyclists undergo cycling reflexivity and examine pre-collision cycling behaviours. Cycling reflexivity as a psychological process guides cycling behavioural change. Cyclists who perceived an internal locus of control altered urban cycling behaviour. Cyclists who perceived an external locus of control resisted behavioural change. Abstract: This study explores whether urban cyclists change on-road cycling behaviour following a collision(s) with a motor vehicle, an area that has not been explored in quantitative and qualitative transportation research. Purposive sampling was employed and data was collected through semi-structured in-depth interviews with 9 males and 9 females from Toronto, Canada. An inductive realist thematic method was used to analyze the data. Overall, three main themes were drawn out: cycling reflexivity, cycling behavioural change and resistance to cycling behavioural change. Eliciting the theme of cycling reflexivity, these findings reveal that all post-collision cyclists actively contemplated behavioural change, and the adoption or resistance toward cycling behavioural change was influenced by intersectional internal and external dispositions emanating from pre-collision cycling behaviours. By adopting general modifications and or defensive cycling practices, in total, 12 cyclists described cycling behavioural change. In contrast, eliciting the resistance toward cycling behavioural change theme, 6 participants indicated that there were no observable modifications in post-collision cycling behaviour. Grounded in the locus of control theory and the health belief model, this study elucidates cycling behavioural change as a psychological and behavioural coping mechanism employed by this particular cohort of cyclists in an effort to mitigate future collisions with motor vehicles. These novel findings set the stage for future research into cyclists' post-collision experiences grounded in psychological and or behavioural research paradigms.